Burkholderia cepacia complex Cervical Osteomyelitis in an Intravenous Drug User. (9th September 2018) - Li, Sui Kwong; Messer, William B.
Abstract : Gram-negative vertebral osteomyelitis infections are increasing due to rising intravenous drug use but overall remain uncommon. Here, we present a case of Burkholderia cepacia complex cervical osteomyelitis in an intravenous drug user. Burkholderia cepacia complex vertebral osteomyelitis has been infrequently described in the literature thus far with varied antibiotic treatment regimens. A 68-year-old male presented to the emergency department with neck pain after minor trauma. He endorsed active intravenous heroin and methamphetamine use. CT and MRI imaging of the cervical spine revealed destructive changes of C5-C6 vertebral bodies consistent with osteomyelitis. Neurological exam was stable and vital signs were within normal limits; so, antibiotics were held, and he was admitted for diagnostic evaluation. Five sets of blood cultures were drawn on admission and were ultimately negative. He subsequently underwent C5-C6 corpectomy, C4-C7 anterior fusion, and C3-T1 posterior fusion with allograft placement. Deep operative tissue cultures grew Burkholderia cepacia complex . He was treated with 6 weeks of intravenous ceftazidime followed by indefinite oral minocycline due to hardware placement. Burkholderia cepacia complex should be considered among pathogenic etiologies of pyogenic vertebral osteomyelitis, particularly among patients with intravenous drug use. Ceftazidime monotherapy was an effective treatment in this particular case.